1995
DOI: 10.1002/polb.1995.090331402
|View full text |Cite
|
Sign up to set email alerts
|

Structure and molecular conformation of tussah silk fibroin films: Effect of methanol

Abstract: Structural changes of tussah (Antheraea pernyi) silk fibroin films treated with different water‐methanol solutions at 20°C were studied as a function of methanol concentration and immersion time. X‐ray diffraction measurements showed that the α‐helix structure, typical of untreated tussah films, did not change for short immersion times (2 min), regardless of methanol concentration. However, crystallization to β‐sheet structure was observed following immersion of tussah films for 30 min in methanol solutions ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
2
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 8 publications
6
88
2
1
Order By: Relevance
“…Considering the conformational structures of a native Antheraea pernyi fibroin film and regenerated fibroin film from lithium thiocyanate solution reported by others, 6,10 it can be concluded that the conformational structure of fibroin film was independent on the dissolution and preparation method and only dependent on the chemical composition of materials.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Considering the conformational structures of a native Antheraea pernyi fibroin film and regenerated fibroin film from lithium thiocyanate solution reported by others, 6,10 it can be concluded that the conformational structure of fibroin film was independent on the dissolution and preparation method and only dependent on the chemical composition of materials.…”
mentioning
confidence: 94%
“…The effects of casting conditions on the molecular conformation of native Antheraea pernyi fibroin films were studied 7,8 and the influence of heat and methanol treatment on the molecular conformation was also investigated. 9,10 The aim of the present work is to prepare the regenerated Antheraea pernyi silk fibroin films from calcium nitrate solution and to investigate the structural and conformational changes of these films induced by immersion in methanol solution with different concentration and time. The X-ray diffraction (XRD) and infrared (IR) spectroscopic method were used for the analysis of the crystalline structure and molecular conformation.…”
Section: Introductionmentioning
confidence: 99%
“…27 The pure TSF showed diffraction peaks at 16.5 , 20.5 and 24.5 corresponding to the spacing of 5.37Å, 4.33Å and 3.63Å, attributing to b-sheet. 38 From the IR analysis, we knew that the molecular interaction between BSF and TSF was absent or very weak. Consistent with these results, the diffraction of the blend lms (b-d) exhibited diffraction peaks' characteristic of BSF and TSF simply overlapping in Fig.…”
Section: 37mentioning
confidence: 99%
“…Different parameters such as methanol, 63 temperature, 64 and pressure 65 were shown to induce the formation of b-sheets in silkworm silk. Other studies performed on B. mori fibroin samples provided useful band assignments of the silk I conformation (the native form found in the spinning dope) and random coil.…”
mentioning
confidence: 99%